Ethnographic Character of the Novel “Vilius Karalius” by Ieva Simonaitytė in the Context of Lithuanian Wedding Customs and Rituals of the 19th – the First Half of the 20th Century - Kavaliauskienė, Aušra Žemyna (Tautosakos darbai, 2019)
The aim of the article is introducing a new approach to the Lithuanian classical novel – “Vilius Karalius” by Ieva Simonaitytė, and appreciating it as an ethnographic source supplying data regarding the wedding customs practiced in the Lithuania Minor in the 19th century and in the first half of the 20th century. The author compares the literary text and the historical ethnographic facts, also paying attention to the dialect peculiarities. More attention is payed to those segments of the wedding that are more or less explicitly depicted in the novel by Simonaitytė (the matchmaking, the bride’s dowry, leaving for the church, gifts, gaubtuvės, etc.). It appears that although the Lithuanian wedding as a whole is not described in “Vilius Karalius”, the relatively numerous fragments of the wedding customs and rituals, as well as other ethnographic details substantially enrich our knowledge of the wedding practices in the 19th – the first half of the 20th century, also revealing the change of the tradition. Research works by Angelė Vyšniauskaitė serve as the ethnological background for the article, since this researcher has studied the Lithuanian wedding customs very actively and in most detail.Ieva Simonaitytė has recorded in her novel some wedding customs and rituals from the Lithuania Minor that are particularly deeply rooted in tradition and vividly reflect the regional peculiarities: i.e., the adorning and “guarding” of the bride’s corner, the ceremonial covering of the bride (gaubtuvės), the gift giving / ransom, etc. Obviously, some unique aspects of making the dowry came into being in the 20th century Klaipėda Region, possibly determined by intense adoption by the inhabitants of the shop-bought clothes instead of the homemade textiles. The woven trousseau survives as a distinctive mark of the wealthy bride upholding the Lithuanian traditions. The professional matchmaking is explicitly described in the novel as well. In the 19th century and in the beginning of the 20th century in the Lithuania Minor, searching for a suitable bride or groom was primarily the women’s business. Spread of pietism and increasing modernization of the society resulted in the negative attitude being increasingly directed at the traditional wedding songs, dances and superstitions of the Lithuania Minor.
Keywords: novel “Vilius Karalius”; Ieva Simonaitytė; the Lithuania Minor; Lithuanian wedding customs